Carbon risk and corporate bankruptcy pressure: evidence from a quasi-natural experiment based on the Paris agreement - Jingxing Liu; Zihang Liao; Tianqi Liu; Yuan Geng (Frontiers in Environmental Science)
Green and low-carbon development transformation of enterprises is of great significance to climate governance and sustainable economic development. It is a realistic problem worth to study whether carbon risk will affect the bankruptcy pressure of corporates. This paper empirically analyzes the impact of carbon risk shocks on the corporates bankruptcy pressure based on the quasi-natural experiment of the implementation of the Paris Agreement. The results indicated that carbon risk significantly alleviated corporates bankruptcy pressure. Specifically, mechanistic analysis uncovered that the increase in carbon risk may reduce the bankruptcy pressure of corporates was mediated by lowering corporate financing costs and elevating green innovation levels. Finally, it was found through the heterogeneity analysis that the negative correlation between carbon risk and bankruptcy pressure was more pronounced for non-state-owned enterprises, small-scale corporations, and companies located in highly competitive industries.